2021
DOI: 10.1002/hyp.14242
|View full text |Cite
|
Sign up to set email alerts
|

A hydropedological approach to simulate streamflow and soil water contents with SWAT+

Abstract: Reflecting internal catchment hydrological processes in hydrological models is important for accurate predictions of the impact of climate and land‐use change on water resources. Characterizing these processes is however difficult and expensive due to their dynamic nature and spatio‐temporal variability. Hydropedology is a relatively new discipline focusing on the synergistic integration of hydrology, soil physics and pedology. Hydropedological interpretations of soils and soil distribution can be used to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…By combining modern digital soil mapping (DSM) techniques (McBratney et al., 2003) with hydropedological insight (Van Tol et al., 2021), soil scientists can now produce detailed large‐scale hydrological soil datasets for modeling purposes (Julich et al., 2012; Van Tol et al., 2015; Van Zijl et al., 2020; Van Tol & Van Zijl, 2022; Wahren et al., 2016). This practice has also been underpinned by several studies, which have indicated that improved soil information does indeed improve hydrological modeling efficiency (Bossa et al., 2012; Diek et al., 2014; Romanowicz et al., 2005; Smit & Van Tol, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…By combining modern digital soil mapping (DSM) techniques (McBratney et al., 2003) with hydropedological insight (Van Tol et al., 2021), soil scientists can now produce detailed large‐scale hydrological soil datasets for modeling purposes (Julich et al., 2012; Van Tol et al., 2015; Van Zijl et al., 2020; Van Tol & Van Zijl, 2022; Wahren et al., 2016). This practice has also been underpinned by several studies, which have indicated that improved soil information does indeed improve hydrological modeling efficiency (Bossa et al., 2012; Diek et al., 2014; Romanowicz et al., 2005; Smit & Van Tol, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The argument is that hydrological soil information may serve as an effective "soft data" tool, especially in ungauged basins where streamflow data is absent, to better represent internal hydrological processes within a catchment [34]. The use of "soft data" in hydrological model configuration and calibration has gained traction in recent years [34][35][36][37], where soft data is defined as information that may not necessarily be measured directly but can be related to a hydrological process or processes.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the pioneering work in South Africa based on modeling the effect of subsurface pedogenic soil horizons on regional flow regimes (Van Tol, 2020; van Tol & van Zijl, 2022; Van Tol et al., 2018; Van Tol et al., 2021). An intriguing example was generated in Oman where soil scientists observed locally vegetated patterns in an otherwise barren sand basin.…”
Section: Why Consider Hydropedology Rather Than Just Soil Physics?mentioning
confidence: 99%